2008
DOI: 10.1185/03007990802083408
|View full text |Cite
|
Sign up to set email alerts
|

Dosage, titration, and gaps in treatment with extended release niacin in clinical practice

Abstract: A considerable proportion of new ER niacin users failed to reach recommended daily maintenance dosages in clinical practice. The main limitations of the study include its reliance on administrative data, inability to capture over-the-counter niacin use, and evaluation of reasons for suboptimal titration. Future research should determine the extent to which gaps in ER niacin therapy and failure to titrate to optimal dosages are due to poor tolerability, physician practice, or other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…In the current study, there was a significantly lower rate of discontinuation due to flushing in the ERN/LRPT group than in the N-ER group (0.8 vs. 3.7%, respectively). These findings are consistent with results from observational studies showing that the frequency and intensity of niacin-induced flushing are critical factors for patients choosing not to titrate or to discontinue niacin therapy, often outweighing the understood clinical benefit [13, 21]. …”
Section: Discussionsupporting
confidence: 80%
“…In the current study, there was a significantly lower rate of discontinuation due to flushing in the ERN/LRPT group than in the N-ER group (0.8 vs. 3.7%, respectively). These findings are consistent with results from observational studies showing that the frequency and intensity of niacin-induced flushing are critical factors for patients choosing not to titrate or to discontinue niacin therapy, often outweighing the understood clinical benefit [13, 21]. …”
Section: Discussionsupporting
confidence: 80%
“…Studies have reported that approximately one-half of patients on ERN therapy reached the recommended daily maintenance dose of 1000 mg or greater during 6.5 months of follow-up (22), most patients took "drug holidays" (22) and discontinuation rates were greater than 50% at one-year follow-up (23). The results of another study (24) also indicated a poor rate of persistence associated with ERN therapy.…”
supporting
confidence: 50%
“…[11][12][13][14] These problems have deterred many patients from adhering to niacin treatment and prevented clinicians from administering a robust therapeutic dose of 1.5 to 2.0 g/day. 15,16 Niacin-induced flushing is mediated primarily by prostaglandin D 2 (PGD 2 ), which stimulates PGD 2 receptor-1 (DP1) in the skin. 17 The mechanisms that produce PGD 2 -mediated flushing and the lipid-modifying effects of niacin 18 are distinct, enabling the development of an agent that inhibits flushing without compromising the efficacy of niacin.…”
mentioning
confidence: 99%